Cita Menuju Ideal Moral Al-Qur'an (Kajian atas Neo-Modernisme Fazlur Rahman) - Hudan Mudaris (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2009)
According to Fazlur Rahman, the interpretation of Qur'an verses should go along with the social changes. Meanwhile, still there is a phenomenon on arguing the best solution; maintaining the classical interpretation or building contextual ones. When changing happened there is a challenge to prove the existence of Qur'an.